Office skills : a practical approach - Horsfall, Margaret. (McGraw-Hill, 1997)
Office role and functions (NOS 120). Office equipment (NOS 109 and 210). Telephone operations (NOS 126). Office supplies (NOS 132). Reception protocal (NOS 137). Personal and team effectiveness at work (NOS 121 and 142). Job seeking (NCS 003). Records management (NOS 108, 208 and 302)...